Conceptualising global water challenges: A transdisciplinary approach for understanding different discourses in sustainable development. (15th November 2021) - Brennan, Michael; Rondón-Sulbarán, Janeet; Sabogal-Paz, Lyda Patricia; Fernandez-Ibañez, Pilar; Galdos-Balzategui, Ane
Abstract: Global challenges impact upon substantial numbers of people in different locations and inform policy at multiple levels under the United Nation's Sustainable Development Goals (SDGs). An aspect of the SDGs framework is the stated inter-relationship between SDGs and local, regional and global partnerships for research and development. In response to dissatisfaction with existing approaches to addressing such complex problems the purpose of this paper is to propose a problem-language-context (PLC) model as a way of framing sustainable development challenges; and in so doing create a heuristic that allows challenges such as water security to be understood using a logically consistent framework. Such an approach builds on a growing transdisciplinary innovation literature that strives to generate knowledge that is problem-focused and inclusive of both scientific and societal stakeholders. The utility of the PLC model is then examined using a case study review carried out on a body of evidence - the United Nations World Water Development Reports (WWDRs) 2003–2019. The result of this review suggests that such problem framing can be of value in revealing the implicit (and sometimes contradictory) assumptions held by policy makers, practitioners and researchers. The main conclusion is that a transdisciplinary approach is one way of better understanding some of the conflicting viewpoints evident in discipline-based approaches to sustainable development, global water challenges and water security. Highlights: Introduces a transdisciplinary approach to global water challenges. Describes a problem-based framework for water research. Presents a meta-ethnographic review of UN World Water Development Reports. Demonstrates the utility of a model for understanding conflicting viewpoints.